A Peer Assisted Learning (PAL) approach to pre-service teacher professional experiences in Australia: organisational friendships. Issue 4 (8th August 2019) - Bone, Kate; Bone, Jane; Grieshaber, Sue; Quinones, Gloria
ABSTRACT: This study explored how students (pre-service teachers) benefit from the support of having a peer with them during their first professional experience in preschool contexts, utilising a PAL (Peer Assisted Learning) approach. International students at a large Australian University were interviewed as part of this qualitative study. We found that peer engagement facilitated the development of friendships and social support among participants. Discussion is situated within a sociological framework of organisational friendship. This study extends conceptions of organisational friendships beyond managerial imperatives and peer relationships are highlighted as supportive, not competitive, engagements. The PAL approach highlights the benefit of collaborative professional learning.